2019
DOI: 10.3390/ijgi8100445
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Bus, Metro, and Taxi Use before and after the Chinese Spring Festival

Abstract: Public transport plays an important role in developing sustainable cities. A better understanding of how different public transit modes (bus, metro, and taxi) interact with each other will provide better sustainable strategies to transport and urban planners. However, most existing studies are either limited to small-scale surveys or focused on the identification of general interaction patterns during times of regular traffic. Transient demographic changes in a city (i.e., many people moving out and in) can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Current spatial network analysis techniques are convenient for exploring the structure of urban agglomerations because they are often tied to mobility‐related big data (e.g., taxi GPS trajectories, social media, smart card data) that can be used to examine spatial interaction patterns (Huang et al, 2019; Liu, Kang, Gao, Xiao, & Tian, 2012; Liu, Sui, Kang, & Gao, 2014). However, the use of spatial networks via mobility big data presents a level of uncertainty, as the revealed spatial structure of an urban agglomeration may be affected by the source of the data.…”
Section: Related Work On Urban Agglomeration Structuresmentioning
confidence: 99%
“…Current spatial network analysis techniques are convenient for exploring the structure of urban agglomerations because they are often tied to mobility‐related big data (e.g., taxi GPS trajectories, social media, smart card data) that can be used to examine spatial interaction patterns (Huang et al, 2019; Liu, Kang, Gao, Xiao, & Tian, 2012; Liu, Sui, Kang, & Gao, 2014). However, the use of spatial networks via mobility big data presents a level of uncertainty, as the revealed spatial structure of an urban agglomeration may be affected by the source of the data.…”
Section: Related Work On Urban Agglomeration Structuresmentioning
confidence: 99%
“…Further, most people travel to different places in their daily life for various activities ( Kwan, 2012 ), and people's daily mobility outside their homes may not be reduced since they still have to obtain groceries, medicines, essential services, or go to work during a pandemic ( Huang et al, 2020 ). Thus, people's daily mobility is also shaped by various built-environment and socio-demographic features, which may in turn render some places more risky than others ( Hutch et al, 2011 ; Huang et al, 2019 ; Lai et al, 2020 ). For instance, using contact tracing data collected in Hong Kong, Huang et al (2020) , Kan et al (2021a , b) , Kwok et al (2021) , and Yip et al (2021) found that certain socio-demographic features (e.g., population density, household income, workplace location, and occupation) and built-environment features (e.g., green space, sky view, building density and height, transport nodal accessibility, land use configuration, and street length) significantly affected the spatial patterns of COVID-19 transmission in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used human mobility data (e.g., smart card data) and spatial networks to examine superspreading places (SSPs). In a spatial network framework, the spatial units (e.g., public transport stations, census tracts, counties) are represented as nodes , and the intensity of human movements between the nodes are presented as weighted edges that indicate the volume of movements among the nodes ( Rizzo et al, 2014 ; Huang et al, 2019 ; Kan et al, 2021c ; Liu et al, 2021 ). In a spatial network, the degree of a node indicates that the number of edges connected to it; the strength of a node refers to the weights of all edges (i.e., the intensity of human movements) connected to it.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the abovementioned data sets, travel data such as currency data [28], mobile phone data [29,33], subway bus card data [34] and floating car data [35,36] are widely used in the analysis of travel behaviors. Among these, the trajectory data of taxicabs record the spatial location more closely to the destination, which is more suitable for fine-grained research.…”
Section: Introductionmentioning
confidence: 99%